# Caleb builds a particle detector and uses it to measure radiation from a remote star. On any given day, the number of particles, Y, that hit the detector is distributed according to a Poisson distribution with parameter x. The parameter x is unknown and is modeled as the value of a random variable X that is exponentially distributed with parameter μ>0:

fX(x)={μe−μx,0,if x≥0,otherwise.

The conditional PMF of the number of particles hitting the detector is

pY∣X(y∣x)=⎧⎩⎨e−xxyy!,0,if y=0,1,2,…,otherwise.

(a) Find the MAP estimate of X based on the observed value y of Y. Express your answer in terms of y and μ. Use 'mu' to denote μ.

x^MAP(y)=- unanswered

(b) Our goal is to find the LMS estimate for X based on the observed particle count y.

We can show that the conditional PDF of X given Y is of the form

fX∣Y(x∣y)=λy+1y!xye−λx,x>0,y≥0.

Express λ as a function of μ. You may find the following equality useful:

∫∞0ay+1xye−axdx=y!,for any a>0.

λ=- unanswered

Find the LMS estimate of X based on the observed particle count y. Express your answer in terms of y and μ. Hint: You may want to express xfX∣Y(x∣y) in terms of fX∣Y(x∣y+1).

x^LMS(y)= - unanswered

## a) y/(1+mu)

b) 1+mu

c) (y+1)/(1+mu)

## Can someone please answer?

## Thanks

## Jacob, can you explain how did you get these answers?

I want understand this problem

## thanks a lot!

## a) To find the Maximum A Posteriori (MAP) estimate of X based on the observed value y of Y, we need to find the value of x that maximizes the posterior probability density function (PDF) of X given Y.

Using Bayes' theorem, the posterior PDF of X given Y is given by:

fX|Y(x|y) = (pY|X(y|x) * fX(x)) / ∫pY|X(y|x') * fX(x') dx'

Since the conditional PMF of Y given X is given as:

pY|X(y|x) = e^(-x) * (x^y / y!)

And the PDF of X (exponential distribution) is given as:

fX(x) = μ * e^(-μx)

Substituting these values into the expression for the posterior PDF, we have:

fX|Y(x|y) = [e^(-x) * (x^y / y!)] * (μ * e^(-μx))

Simplifying this expression, we get:

fX|Y(x|y) = (μ * x^y * e^(-x(1+μ))) / y!

To find the MAP estimate of X, we need to find the value of x that maximizes the posterior PDF. This is equivalent to finding the value of x that maximizes the numerator of the expression above, since the denominator (y!) does not depend on x.

Taking the logarithm of the numerator, we have:

log(fX|Y(x|y)) = log(μ) + y * log(x) - x(1+μ)

To find the maximum, we take the derivative of this expression with respect to x and set it equal to zero:

d/dx [log(fX|Y(x|y))] = (y/x) - (1+μ) = 0

Solving for x, we get:

y/x = 1+μ

x^MAP(y) = y / (1+μ)

Therefore, the MAP estimate of X based on the observed value y of Y is x^MAP(y) = y / (1+μ).

b) The conditional PDF of X given Y is given as:

fX|Y(x|y) = λ * (y+1) * x^y * e^(-λx)

To find the LMS estimate of X based on the observed particle count y, we need to find the value of x that minimizes the mean squared error (MSE) between the estimated value of X and the true value.

The MSE can be calculated as:

MSE = E[(X - x^LMS(y))^2]

To minimize the MSE, we take the derivative of the MSE with respect to x and set it equal to zero:

d/dx [MSE] = d/dx [E[(X - x^LMS(y))^2]] = 0

Expanding this expression and simplifying, we get:

2 * E[(X - x^LMS(y))] * (-1) = 0

Solving for E[(X - x^LMS(y))], we find:

E[(X - x^LMS(y))] = 0

To find x^LMS(y), we calculate the expectation of X given Y:

E[X|Y=y] = ∫x * fX|Y(x|y) dx

Substituting the expression for fX|Y(x|y) from part b), we have:

E[X|Y=y] = ∫x * λ * (y+1) * x^y * e^(-λx) dx

Simplifying this expression and using the given equality, we find:

E[X|Y=y] = (y+1) / λ

Therefore, the LMS estimate of X based on the observed particle count y is x^LMS(y) = (y+1) / λ.

To find the value of λ, we need to calculate the expected value of Y given X:

E[Y|X=x] = ∑y * pY|X(y|x)

Using the given conditional PMF, we have:

E[Y|X=x] = ∑y * e^(-x) * (x^y / y!)

Simplifying this expression, we find:

E[Y|X=x] = x * e^(-x) * ∑(y+1) * (x^y / (y+1)!)

Using the given equality, we know that ∑(y+1) * (x^y / (y+1)! = e^x

Therefore, E[Y|X=x] = x * e^(-x) * e^x = x

Since the expected value of Y given X is x, we have λ = E[Y|X] = E[X] = μ.

Therefore, the LMS estimate of X based on the observed particle count y is x^LMS(y) = (y+1) / μ.

## (a) To find the Maximum A Posteriori (MAP) estimate of X based on the observed value y of Y, we need to find the value of x that maximizes the conditional posterior probability distribution of X given Y.

Using Bayes' theorem, the conditional posterior probability distribution can be obtained as:

pX∣Y(x∣y) = pY∣X(y∣x) * pX(x) / pY(y)

Where pX(x) is the prior distribution of X and pY(y) is the marginal distribution of Y. Since the question does not provide any information about the prior distribution or the marginal distribution, we cannot find the exact MAP estimate of X in terms of y and μ.

(b) To find the Least Mean Squares (LMS) estimate of X based on the observed particle count y, we need to minimize the mean squared error between the estimated value of X and its true value.

The conditional probability density function (PDF) of X given Y is given as:

fX∣Y(x∣y) = λ * (y + 1) * (x^y) * e^(-λx)

where λ is a parameter to be determined.

To find λ, we can integrate fX∣Y(x∣y) with respect to x from 0 to infinity and equate it to y!:

∫∞0 λ * (y + 1) * (x^y) * e^(-λx) dx = y!

Using the provided equality:

∫∞0 ax^(y+1) * e^(-ax) dx = y!

Comparing the two equations, we can see that λ = μ, where μ is the parameter of the exponential distribution of X.

Now, we can express xfX∣Y(x∣y) in terms of fX∣Y(x∣y+1):

xfX∣Y(x∣y) = (y + 1) * (x^y) * e^(-μx)

The LMS estimate of X can be obtained by multiplying xfX∣Y(x∣y) with x and integrating it from 0 to infinity:

x^LMS(y) = ∫∞0 [(y + 1) * (x^y) * e^(-μx)] * x dx

Integrating this expression will result in the LMS estimate of X in terms of y and μ. However, the integration process may involve complex mathematical calculations. Therefore, the exact expression cannot be provided without performing the integration.